LRRC56 deficiency cause motile ciliopathies in humans and mice - Xie, Xiao-Hui; Gu, Heng; Yang, Jun-Lin; Yuan, Zhuang-Zhuang; Qin, Ke-Le; Tan, Zhi-Ping (Frontiers in Genetics, 2025)
IntroductionMotile ciliopathies represent a group of disorders caused by impaired motility of cilia and flagella, resulting in clinical manifestations such as laterality defects, asthenospermia, chronic respiratory infections, and hydrocephalus. Although nearly 53 genes have been implicated, the genetic etiology remains unresolved in approximately 30% of cases, and the regulatory mechanisms of motile ciliogenesis are still incompletely understood.MethodsWhole-exome sequencing was employed in a patient with laterality defects and recurrent pulmonary infections. Nasal epithelial brushings underwent high-speed video microscopy (HSVM) to evaluate ciliary beat pattern, and conventional transmission electron microscopy (TEM) to assess ultrastructure. CRISPR/Cas9 technology was harnessed to generate precise Lrrc56 knockout mice. Quantitative proteomics was conducted on Lrrc56-deficient compared with wild-type tissues to explore the mechanisms.ResultsWhole exome sequencing identified a novel homozygous frameshift variant in LRRC56 (c.148delG, p. Val50Trpfs*22) in the proband. HSVM of nasal cilia from the proband demonstrated severely dyskinetic motion, despite the absence of obvious ultrastructural defects on conventional TEM. Lrrc56-knockout mice recapitulated the patient’s laterality defects and also exhibited additional phenotypes consistent with motile ciliopathies, including male infertility, hydrocephalus, and defective mucociliary clearance. Quantitative proteomic analysis revealed markedly reduced expression of cilia-associated proteins, particularly microtubule inner proteins (MIPs) and axonemal dynein assembly factors, in Lrrc56-deficient tissues compared with wild-type controls.DiscussionOur findings establish LRRC56 as an essential regulator of ciliary motility and highlight its role in the pathogenesis of motile ciliopathies.